The addition of low‐dose‐rate brachytherapy and androgen‐deprivation therapy decreases biochemical failure and prostate cancer death compared with dose‐escalated external‐beam radiation therapy for high‐risk prostate cancer1. Issue 3 (14th August 2012) - Shilkrut, Mark; Merrick, Gregory S.; McLaughlin, P. William; Stenmark, Matthew H.; Abu‐Isa, Eyad; Vance, Sean M.; Sandler, Howard M.; Feng, Felix Y.; Hamstra, Daniel A.
Abstract BACKGROUND: The objective of this study was to determine whether the addition of low‐dose‐rate brachytherapy or androgen‐deprivation therapy (ADT) improves clinical outcome in patients with high‐risk prostate cancer (HiRPCa) who received dose‐escalated radiotherapy (RT). METHODS: Between 1995 and 2010, 958 patients with HiRPCa were treated at Schiffler Cancer Center (n = 484) or at the University of Michigan (n = 474) by receiving either dose‐escalated external‐beam RT (EBRT) (n = 510; minimum prescription dose, 75 grays [Gy]; median dose, 78 Gy) or combined‐modality RT (CMRT) consisting of 103Pd implants (n = 369) or 125I implants (n = 79) both with pelvic irradiation (median prescription dose, 45 Gy). The cumulative incidences of biochemical failure (BF) and prostate cancer‐specific mortality (PCSM) were estimated by using the Kaplan‐Meier method and Fine and Gray regression analysis. RESULTS: The median follow‐up was 63.2 months (interquartile range, 35.4‐99.0 months), and 250 patients were followed for >8 years. Compared with CMRT, patients who received EBRT had higher prostate‐specific antigen levels, higher tumor classification, lower Gleason sum, and more frequent receipt of ADT for a longer duration. The 8‐year incidence BF and PCSM among patients who received EBRT was 40% (standard error, 38%‐44%) and 13% (standard error, 11%‐15%) compared with 14% (standard error, 12%‐16%; P < .0001) and 7% (standard error 6%‐9%; P = .003) among patients who received CMRT. On multivariate analysis, the hazard ratios (HRs) for BF and PCSM were 0.35 (95% confidence interval [CI], 0.23‐0.52; P < .0001) and 0.41 (95% CI, 0.23‐0.75; P < .003), favoring CMRT. Increasing duration of ADT predicted decreased BF (P = .04) and PCSM (P = .001), which was greatest with long‐term ADT (BF: HR, 0.33; P < .0001; 95% CI, 0.21‐0.52; PCSM: HR, 0.30; P = .001; 95% CI, 0.15‐0.6) even in the subgroup that received CMRT. CONCLUSIONS: In this retrospective comparison, both low‐dose‐rate brachytherapy boost and ADT were associated with decreased risks of BF and PCSM compared with EBRT. Cancer 2013. © 2012 American Cancer Society.